Inner Nuclear Membrane Protein, SUN1, is Required for Cytoskeletal Force Generation and Focal Adhesion Maturation - Ueda, Nanami; Maekawa, Masashi; Matsui, Tsubasa S.; Deguchi, Shinji; Takata, Tomoyo; Katahira, Jun; Higashiyama, Shigeki; Hieda, Miki (Frontiers in Cell and Developmental Biology, 2022)
The linker of nucleoskeleton and cytoskeleton (LINC) complex is composed of the inner nuclear membrane-spanning SUN proteins and the outer nuclear membrane-spanning nesprin proteins. The LINC complex physically connects the nucleus and plasma membrane via the actin cytoskeleton to perform diverse functions including mechanotransduction from the extracellular environment to the nucleus. Mammalian somatic cells express two principal SUN proteins, namely SUN1 and SUN2. We have previously reported that SUN1, but not SUN2, is essential for directional cell migration; however, the underlying mechanism remains elusive. Because the balance between adhesive force and traction force is critical for cell migration, in the present study, we focused on focal adhesions (FAs) and the actin cytoskeleton. We observed that siRNA-mediated SUN1 depletion did not affect the recruitment of integrin β1, one of the ubiquitously expressed focal adhesion molecules, to the plasma membrane. Consistently, SUN1-depleted cells normally adhered to extracellular matrix proteins, including collagen, fibronectin, laminin, and vitronectin. In contrast, SUN1 depletion reduced the activation of integrin β1. Strikingly, the depletion of SUN1 interfered with the incorporation of vinculin into the focal adhesions, whereas no significant differences in the expression of vinculin were observed between wild-type and SUN1-depleted cells. In addition, SUN1 depletion suppressed the recruitment of zyxin to nascent focal adhesions. These data indicate that SUN1 is involved in the maturation of focal adhesions. Moreover, disruption of the SUN1-containing LINC complex abrogates the actin cytoskeleton and generation of intracellular traction force, despite the presence of SUN2. Thus, a physical link between the nucleus and cytoskeleton through SUN1, but not SUN2, is required for the proper organization of actin, thereby suppressing the incorporation of vinculin and zyxin into focal adhesions and the activation of integrin β1, both of which are dependent on traction force. This study provides insights into a previously unappreciated signaling pathway from the nucleus to the cytoskeleton, which is in the opposite direction to the well-known mechanotransduction pathways from the extracellular matrix to the nucleus.